Estresse oxidativo em duas espécies de teleósteos amazônicos, Astronotus ocellatus e Colossoma macropomum, expostos a diferentes tensões de oxigênio: uma abordagem comparativa - Marcon, Jaydione Luiz (Instituto Nacional de Pesquisas da Amazônia - INPA, 1996)
This study describes the antioxidant defenses of acará-açu (Astronotus ocellatus) and tambaqui (Colossoma macropomum) exposed to long term hypoxia, normoxia and hyperoxia. Superoxide dismutase, catalase and the oxidized cell products (measured as TBARS) were measured in liver and blood of A. ocellatus and C. macropomum. Methemoglobin and glutathione contents were evaluated only in the blood and glutathione peroxidase only in the liver. These species exhibit different responses for the analysed parameters. Acclimation to hypoxia resulted in increased methemoglobin and liver superoxide dismutase levels in C. macropomum. Glutathione peroxidase also increased in both species, whereas reduced glutathione decreased in hypoxia exposed animals. Colossoma macropomum exhibited acatalasemia in normoxia and hypoxia, while catalase decreased in A. ocellatus exposed to hypoxia. Under hyperoxia, most of the analyzed parameters were changed significantly in both liver (increased TBARS, superoxide dismutase and glutathione peroxidase levels, and a possible inhibition of catalase) and blood (increased methemoglobin, TBARS and superoxide dismutase levels) of C. macropomum. In addition, a high production of intraerythrocytic oxidized glutathione was also observed in C. macropomum. Astronotus ocellatus exhibited slight changes in antioxidant defenses and no cellular damage in both liver and blood. This cichlid species is hypoxia tolerant and is also able to survive many hours under anoxia, whereas C. macropomum relies preferentially on aerobic metabolism, and is able to improve many adaptive solutions to maintain an adequate oxygen supply to the tissues. We suggest that the responses observed for these fish species to hypoxia and hyperoxia are in agreement to their oxygen needs, where C. macropomum is more susceptible to oxidative stress, specially under hyperoxia.
Keywords: Colossoma macropomum; Astronotus ocellatus; Estresse oxidativo; Normóxia; Colossoma macropomum; Astronotus ocellatus